Manufacturing of dental pulp cell-based products from human third molars: current strategies and future investigations - Ducret, Maxime; Fabre, Hugo; Degoul, Olivier; Atzeni, Gianluigi; McGuckin, Colin; Forraz, Nico; Alliot-licht, Brigitte; Mallein-Gerin, Frédéric; Groult, Emeline; FARGES, Jean-Christophe (Frontiers in Physiology, 2015)
In recent years, mesenchymal cell-based products have been developed to improve surgical therapies aimed at repairing human tissues. In this context, the tooth has recently emerged as a valuable source of stem/progenitor cells for regenerating orofacial tissues, with easy access to pulp tissue and high differentiation potential of dental pulp mesenchymal cells. International guidelines now recommend the use of standardized procedures for cell isolation, storage and expansion in culture to ensure optimal reproducibility, efficacy and safety when cells are used for clinical application. However, most dental pulp cell-based medicinal products manufacturing procedures may not be fully satisfactory since they could alter the cells biological properties and the quality of derived products. Cell isolation, enrichment and cryopreservation procedures combined to long-term expansion in culture media containing xeno- and allogeneic components are known to affect cell phenotype, viability, proliferation and differentiation capacities. This article focuses on current manufacturing strategies of dental pulp cell-based medicinal products and proposes a new protocol to improve efficiency, reproducibility and safety of these strategies.